Korelasi Penguasaan Konsep Dan Sikap Ilmiah Terhadap Kecerdasan Spiritual Siswa Dalam Pembelajaran Pendidikan Agama Islam - Nuraini, Inoh; Sukarno, Sukarno; Huda, Syamsul (Universitas Pakuan, 2025)
This study aims to examine the correlation between concept mastery and scientific attitudes on students' spiritual intelligence in the context of Islamic Religious Education. The research was conducted at Madrasah Aliyah Raudhatul Mujawwidin in Tebo Regency, Jambi Province. A quantitative approach with a survey method was used. The sample consisted of 70 students selected through purposive sampling. The research instrument employed questionnaires, and data were analyzed using SPSS version 25. The results showed a significant correlation between concept mastery and spiritual intelligence at 1%. However, no significant correlation was found between scientific attitude and spiritual intelligence (significance value 0.136 0.05). Simultaneously, concept mastery and scientific attitude showed a significant correlation with students' spiritual intelligence at 18%, with the value of Fcount Ftable (4.18 4.10). These findings highlight the importance of integrating conceptual mastery and scientific attitudes in efforts to strengthen students' spiritual intelligence.